Establishment of age-related AMH screening cutoffs in Chinese women with PCOS: a retrospective study using propensity score matching analysis - Zhen Wang; Xiaojing Teng; Yanfei Liu; Yonghai Shen; Lin Ma; Yu Chen (BMC Endocrine Disorders)
Abstract Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder that affects 5–18% of women worldwide. This disorder is characterized by two core pathological features: ovulatory dysfunction and hyperandrogenism. Method A retrospective analysis was conducted on cases treated at Hangzhou Women’s Hospital from July 2021 to November 2023. Based on age, we conducted propensity score matching analysis in a 1:1 ratio and statistical analysis using SPSS software, plotted receiver operating characteristic curves, and obtained the area under the curve, the optimal anti-Müllerian hormone screening threshold, corresponding sensitivity, specificity, Youden index, correct diagnostic rate, positive predictive value, negative predictive value. Age-related anti-Müllerian hormone screening criteria with polycystic ovary syndrome were established and evaluated based on the optimal anti-Müllerian hormone screening cutoff for each group. The above results were validated by the validation group. And Kappa consistency test was conducted between the age-related anti-Müllerian hormone screening test and 2003 Rotterdam criteria for polycystic ovary syndrome. Results The screening criteria for age-related anti-Müllerian hormone with polycystic ovary syndrome were: ≥7.46 ng/ml (20-24-year-old), ≥ 4.55 ng/ml (25-29-year-old), ≥ 4.19 ng/ml (30-34-year-old), ≥ 3.57 ng/ml (35-39-year-old). Conclusion Our research indicates that age specific AMH threshold values show promising sensitivity and specificity for PCOS screening in the validation cohort. These findings indicate the potential utility of AMH based screening, but emphasize the need for optimization and validation in larger multicenter studies before clinical implementation. Clinical trial number Not applicable.